Tailoring the Photoluminescence Excitation Dependence of the Carbon Dots via an Alkali Treatment - Zhao, Yun Yang; Qu, Song Nan; Feng, Xi Yuan; Xu, Jin Cheng; Yang, Ye; Su, Shi Chen; Wang, Shuang Peng; Ng, Kar Wei (The journal of physical chemistry letters, 2019)
Carbon dots (CDs) have shown great potential in various applications including biomedicines and optoelectronics. However, the origin of their photoluminescence excitation dependence (PL-ED) still remains uncertain, and this can limit the full exploit of their wonderful optical properties. Here we studied the mechanism for the PL-ED of solvothermally synthesized CDs using an alkali treatment. As-synthesized CDs were found to agglomerate and exhibited multicolor emissions with strong PL-ED. The alkali treatment can effectively break down the clusters into individual CDs via the hydrolysis of the amide and ester bonds that link the CDs together. This process effectively narrowed the emission line width and suppressed the observed PL-ED. The understanding of the excitation dependence mechanism here outlined a novel strategy for tailoring of the PL-ED of CDs via a synergy of chemical and physical processes, thus enhancing the versatility of CDs for a broader spectrum of applications.